Factors determining outcomes in grown up patients operated for congenital heart diseases - Sachin Talwar; Manikala V Kumar; Vishnubhatla Sreenivas; Shiv K Choudhary; Manoj Sahu; Balram Airan (Wolters Kluwer Medknow Publications, 2016)
Background: The number of grown ups with congenital heart diseases (GUCHs) is steadily increasing. Aims: To analyze factors predicting early cardiac morbidity following cardiac surgery in GUCH at a tertiary care center. Setting and Design: Retrospective study at a multispeciality tertiary referral center. Methods: Between January 2004 and December 2014, 1432 patients ≥13 years of age (acyanotic defects: 843, cyanotic defects: 589) underwent surgery for congenital heart defects. Factors associated with early cardiac morbidity were analyzed. Statistical Analysis: Univariable and multivariable analysis of all factors affecting outcomes. Results: On multivariate analysis, previous sternotomy, aortic cross-clamp time. >45 min, cyanosis, and emergency procedure were independent predictors of early morbidity with respective odds ratios. (ORs) of 12.4, 3.6, 2.6, and 8.1. For more precise estimation, a risk score was generated. Taking the log odds with each of these four as respective weights, a score was generated. The variables were. previous sternotomy. (2.5), aortic cross.clamp. >45 min. (1.3), emergency procedure. (2.1), and cyanosis. (0.9), if the respective condition is present, zero otherwise. The score ranged from 0 to 4.5. The average value of the score based on the four variables was significantly higher in cases with morbidity. (1.85. ± 1.17) vs. (0.75. ± 0.88), P < 0.001. Distribution of scores was significantly different between patients with and without morbidity. Sixty-seven percent patients without any morbidity had score. <1 compared to 24.6% with morbidity. Only 0.9% patients without morbidity had score of ≥3 compared to 16.4% patients with morbidity. Compared with patients having score. <1, patients with scores 1-2 had OR of 3.4, 2.3 had OR of 6.0, and. >3 had OR of 48.7. Conclusion: GUCH can be safely operated when adequate caution is taken in the presence of independent predictors such as previous sternotomy, aortic clamp time >45 min, cyanosis, and emergency procedure.